Análisis de la estructura del formato reality show y del lenguaje televisivo del programa BLN La Competencia, y su influencia mediática en la ciudad de Guayaquil - Sánchez Echeverría, Mayra Elizabeth (2019)
The reality show, in Spanish reality TV shows, appeared in the 70s in the United States. The first to go on the air was An American Family, which consisted in showing the television of the coexistence of a family seven days a week. And that is precisely what this type of programs seek, described by some authors as "telebasura", since they have nothing to contribute. According to what Perales explained, reality shows expose the coexistence of a group of people, who try to overcome their rivals through a competition, which is exposed to the audience. Currently, there are different classes, however the common denominator of almost all these programs, which still have a global reception, is competition and romantic-sexual relationships. This research seeks to analyze the format and language of the case under study: BLN La Competencia, and the media influence that this program has on young people between 18 and 25 years old…….